Algorithms for Enhanced Security and Data Sharing in Blockchain-Driven Healthcare Systems - G. Jithender Reddy; T. Uma Devi (International Journal of Computational and Experimental Science and Engineering, 2025)
In the era of blockchain-driven healthcare systems, sharing and storing secure data has emerged as one of the pivotal challenges. The framework employs Advanced Encryption Standard with Galois/Counter Mode (AES-GCM) to securely encrypt data, including customer and product information, to ensure confidentiality and integrity. Utilizing a new method for Diffie-Hellman key exchange and ring signatures, it is possible to share encryption keys alongside an option anon securely, which are significantly improved to 2.3 and 1.8 seconds, respectively. The blockchain implements Proof-of-Authority (PoA), which allows for high throughput and a low latency response suitable for time-sensitive healthcare applications. A comprehensive real-world dataset of electronic health records (the MIMIC-III Clinical Database) was utilized to evaluate the framework's performance. Compared to state-of-the-art methods, the encryption and decryption times for 50 MB of data have significantly improved to 2.3 seconds and 1.8 seconds, respectively. It is also scalable, which means it scales up as the volume of work increases, and the privacy/security standards can be sustained as the workload increases. This framework covers areas of the regulatory requirements for efficient, secure healthcare data handling, including anonymity, non-repudiation, and data resistance to tampering. Compared with traditional models, it achieves better results regarding execution time, scalability, and data-sharing privacy.